2013
DOI: 10.1007/s00216-013-7234-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of urine and blood plasma in rat models of drug addiction on the basis of morphine, methamphetamine, and cocaine-induced conditioned place preference

Abstract: The metabolic profiles of urine and blood plasma in drug-addicted rat models based on morphine (MOR), methamphetamine (MA), and cocaine (COC)-induced conditioned place preference (CPP) were investigated. Rewarding effects induced by each drug were assessed by use of the CPP model. A mass spectrometry (MS)-based metabolomics approach was applied to urine and plasma of MOR, MA, and COC-addicted rats. In total, 57 metabolites in plasma and 70 metabolites in urine were identified by gas chromatography-MS. The meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 43 publications
5
66
0
1
Order By: Relevance
“…Using nontargeted mass spectrometry to analyze the neurometabolome is a novel technique that has so far been rarely used on brain tissue (Masuo et al, 2009;Deng et al, 2012;Zaitsu et al, 2013), especially not to discern subregions of the brain. The mass spectrometric method used here allows rapid assessment of the complete metabolome with very high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Using nontargeted mass spectrometry to analyze the neurometabolome is a novel technique that has so far been rarely used on brain tissue (Masuo et al, 2009;Deng et al, 2012;Zaitsu et al, 2013), especially not to discern subregions of the brain. The mass spectrometric method used here allows rapid assessment of the complete metabolome with very high resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicates that the metabolic pathways identified from the significantly different metabolites (SDMs) between the OA and PA groups are in line with classic metabolism and represent a typical characteristic of the dietary or medical intervention on organisms (Rocha et al., ; Sun et al., ). It has been known that the number of metabolites detected by GC–MS in plasma varies among animal taxa (Kodama et al., ; Psychogios et al., ; Sun et al., ; Zaitsu et al., ). In the present study, we detected 222 peaks with identification, and among them, 69 metabolites (31.1%) had a similarity >700.…”
Section: Discussionmentioning
confidence: 99%
“…Os avanços na tecnologia em saúde, especialmente com estudos conduzidos em humanos e animais na área da metabolômica, permitiram que nos últimos anos se detectassem milhares de novos marcadores que possam definir perfis bioquímicos de drogadição, de forma a demonstrar os efeitos das drogas no funcionamento fisiológico do corpo, com a possibilidade de associa-las a fatores ambientais e entender mudanças metabólicas correspondentes à sua dependência, abstenção, tratamento e recaída (GHANBARI, SUMNER, 2018). Um desses estudos avaliou perfis metabólicos da urina e plasma de ratos viciados em morfina, meta-anfetamina e cocaína, de forma que o nível de vários metabólitos (ácido 3-hidroxibutírico, L-triptofano, cistina, lactose) estava alterado de acordo com o tipo de amostra e de droga, o que pode demonstrar as diferentes ações de diversas drogas nos circuitos de recompensa cerebrais e apresentar utilidade no entendimento da adição em drogas (ZAITSU et al, 2014…”
Section: Fundamentação Teóricaunclassified